'Cognitive biases plus': covert subverters of healthcare evidence. Issue 2 (26th November 2015) - Seshia, Shashi S; Makhinson, Michael; Young, G Bryan
Abstract : The evidence-based medicine (EBM) paradigm has been associated with many benefits, but there have also been 'some negative consequences'. In part, the consequences may be attributable to: (1) limitations in some of the tenets of EBM, and (2) flawed or unethical decisions in healthcare related organisations. We hypothesise that at the core of both is a cascade of predominantly unconscious cognitive processes we have syndromically termed 'cognitive biases plus', with conflicts of interest (CoIs) as crucial elements. CoIs (financial, and non-financial including intellectual) catalyse self-serving bias and a cascade of other 'cognitive biases plus' with several reinforcing loops. Authority bias, herd effect, scientific inbreeding, replication publication biases, and ethical violations (especially subtle statistical), are key contributors to the cascade; automation biases through uncritical use of statistical software and applications (apps) of preappraised sources of evidence at point of care, may be other increasingly important factors. The 'cognitive biases plus' cascade which involves several intricately connected healthcare-related organisations has the potential to facilitate, compound and entrench flaws in the paradigm, evidence and decisions that converge to inform person-centered healthcare. Our reasoning is based on observational data and opinion. However, the susceptibility of all humans to 'cognitive biases plus' makes our hypothesis plausible. Individual and collective fallibility may be minimised and the quality of healthcare decisions (including those related to improving EBM) enhanced by being conscious of our vulnerability and open-minded to the 'outside view'.